Evaluation of Phytotoxicity of Some Fungicides in Chilli Crop (Journal of Plant Disease Sciences, 2019)
Chilli crop is attacked by number of disease mostly caused by fungal and viral pathogens, The disease of common occurrence in India and specially in Maharashtra are powdery mildew, leaf curling, dieback, root rot and wilt. For controlling such destructive diseases, non judicious and indiscriminate use of some chemicals are harmful to the plant and may exhibit the phytotoxic effect. It was therefore thought necessary to wotkout the phytotoxicity of different spray fungicides,
Keywords: Phytotoxicity; chilli; fungicide; higher doses